Malacofauna (Mollusca: Gastropoda) community structure in a protected landscape of Tabunan Forest, Cebu City, Philippines - RAAMAH ROSALES; LEA COLITA; ZERRY AYN RETUBADO; JOED CABALLERO; EDGARDO LILLO; ARCHIEBALD BALTAZAR MALAKI; RENISSA QUIÑONES; EMMA SACAN (Society for Indonesian Biodiversity, 2025)
Abstract. Rosales R, Colita L, Retubado ZA, Caballero J, Lillo E, Malaki AB, Quiñones R, Sacan E. 2025. Malacofauna (Mollusca: Gastropoda) community structure in a protected landscape of Tabunan Forest, Cebu City, Philippines. Biodiversitas 26: 2631-2639. Malacofauna play a crucial role in sustaining the ecological health of forest ecosystems. They serve as an essential food source for other organisms and play a key role in nutrient cycling. This study aimed to establish an inventory of terrestrial snails in a protected landscape of Tabunan Forest, Cebu Island, Philippines. A two-person team conducted sampling on three permanent plots. The study listed 57 individuals represented by 11 species belonging to nine genera and eight families. Seven families belong to the air-breathing pulmonate group, Order Stylommatophora: Helicinidae, Chronidae, Bradybaenidae, Achatinidae, Trochomorphidae, Zoonitidae, and Camaenidae. One family belongs to the prosobranch group, Order Caenogastopoda: Cyclophoridae. The most abundant were Geophorus acutus and Geophorus agglutinans. Ryssota oweniana has the widest geographical distribution with 100% constancy rate with recorded occurrence in all plots. Seven out of 11 species were recorded only in one plot while two species were recorded in two plots. The result showed a highly restricted distribution of the land snail species in the protected landscape. The limited geographic distribution can adversely affect the reproduction capacity and population growth of the land snail species. The low population density may also indicate that the forest is undergoing environmental pressure either from human activities or climatic change. It is recommended that future studies be conducted to monitor the status of the land snail population within the protected landscape.